Pattern of oral‐maxillofacial trauma from violence against women and its associated factors. Issue 3 (14th March 2017) - da Nóbrega, Lorena Marques; Bernardino, Ítalo de Macedo; Barbosa, Kevan Guilherme Nóbrega; e Silva, Jéssica Antoniana Lira; Massoni, Andreza Cristina de Lima Targino; d'Avila, Sérgio
Abstract: Background/Aim: Violence against women is a global public health problem. The aim of this study was to characterize the profile of women victims of violence and identify factors associated with maxillofacial injuries. Material and Methods: A cross‐sectional study was performed based on an evaluation of 884 medico‐legal and social records of women victims of physical aggression treated at the Center of Forensic Medicine and Dentistry in Brazil. The variables investigated were related to the sociodemographic characteristics of victims, circumstances of aggressions, and patterns of trauma. Descriptive and multivariate statistics using decision tree analysis by the Chi‐squared automatic interaction detector (CHAID) algorithm, as well as univariate and multivariate Poisson regression analyses were performed. Results: The occurrence of maxillofacial trauma was 46.4%. The mean age of victims was 29.38 (SD=12.55 years). Based on decision tree, the profile of violence against women can be explained by the aggressor's gender ( P <.001) and sociodemographic characteristics of victims, such as marital status ( P =.001), place of residence ( P =.019), and educational level ( P =.014). Based on the final Poisson regression model, women living in suburban areas were more likely to suffer maxillofacial trauma (PR=1.752; CI 95%=1.153‐2.662; P =.009) compared to those living in rural areas. Moreover, aggression using a weapon resulted in a lower occurrence of maxillofacial trauma (PR=0.476; CI 95%=0.284‐0.799; P =.005) compared to cases of aggression using physical force. Conclusions: The prevalence of oral‐maxillofacial trauma was high, and the main associated factors were place of residence and mechanism of aggression.